2010
DOI: 10.1016/j.bbabio.2010.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Communication between mitochondria and nucleus: Putative role for VDAC in reduction/oxidation mechanism

Abstract: Voltage dependent anion channel (VDAC) was identified in 1976 and since that time has been extensively studied. It is well known that VDAC transports metabolites across the outer mitochondrial membrane. The simple transport function is indispensable for proper mitochondria functions and, consequently for cell activity, and makes VDAC crucial for a range of cellular processes including ATP rationing, Ca2+ homeostasis and apoptosis execution. Here, we review recent data obtained for Saccharomyces cerevisiae cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…In this context, it is noteworthy that the interaction of GAPDH with VDAC had been shown to be inhibited by DTT treatment in human cell lines (Tarze et al, 2007). In yeast, a central role of VDAC in transducing the cellular redox-state to the nucleus has been suggested (Galganska et al, 2010). In mammals, physical binding of GAPDH to VDAC1 was suggested to induce mitochondrial membrane permeabilization and apoptosis (Tarze et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is noteworthy that the interaction of GAPDH with VDAC had been shown to be inhibited by DTT treatment in human cell lines (Tarze et al, 2007). In yeast, a central role of VDAC in transducing the cellular redox-state to the nucleus has been suggested (Galganska et al, 2010). In mammals, physical binding of GAPDH to VDAC1 was suggested to induce mitochondrial membrane permeabilization and apoptosis (Tarze et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Other processes where a role for YVDAC1 has been proposed include as a channel for metabolites such as NADH, and as a conduit for reactive oxygen species (ROS) signaling via redox regulation and consequent regulation of mRNA and protein levels in the cell. [20,21,22,23]. YDAC1 has been hypothesized to control cellular redox states by the transport of ROS species such as the superoxide anion (O2) across the MOM, and this in term is known to affect cellular mRNA and protein levels (reviewed in Ref.…”
Section: Yeast Vdac Isoformsmentioning
confidence: 99%
“…YDAC1 has been hypothesized to control cellular redox states by the transport of ROS species such as the superoxide anion (O2) across the MOM, and this in term is known to affect cellular mRNA and protein levels (reviewed in Ref. [21]). Over-expression or POR1 complementation in yeast of yeast, fruit fly and mammalian VDACs has also been an important tool in isolating abundant amounts of purified VDAC protein and examining the consequences of engineered point mutations with regard to structure and function [10,24,25].…”
Section: Yeast Vdac Isoformsmentioning
confidence: 99%
“…Previous data demonstrated that Hsp70 (c-Jun N-terminal kinase), crystallins (Akt), and the increased expression of VDAC might be involved in AMD progression [3,18,45,46]. Altered phosphorylations of mitochondrial heat shock protein mtHsp70, αA/αB crystalline, vimentin, and ATP synthase were observed in RPE cell death under oxidative stress [16,47].…”
Section: Discussionmentioning
confidence: 99%